Exploring the Endowment of Ethnic Tourism: A Case Study in Sustainable Rural of Mentaraman - Yunika Puspasari Emma; Haslinda Noor; Purboyo Priambodo Magistyo; Istiqomah Ni’matul (E3S Web of Conferences)
Mentaraman is a rural area with local culture and natural potential. Located on the outskirts of the region, this rural offers authentic cultural and natural experiences for tourists beauty and diversity. This research aims to analyze the potential and challenges in developing Mentaraman Cultural Tourism using Spradley’s qualitative approach. The results of the research show that Mentaraman has a rich cultural heritage, including traditional traditions, local arts and culinary diversity, which is the main attraction for tourists looking for authentic cultural experience. However, the research also identified a number of challenges, including infrastructure problems, resource management, and community participation in decision making related to tourism development. The implications of this research include the need for a holistic and sustainable approach in tourism development, taking into account the interests and aspirations of local communities as well as preserving cultural heritage and the environment. In addition, the active participation of local communities in the management and promotion of tourism is a key factor in developing Mentaraman as a sustainable tourist destination. By involving local residents in every stage of development, such as cultural preservation, infrastructure improvements, and destination marketing, these hamlets can provide significant economic and social benefits to their communities.